The Use of 30% Sucrose and Non-Nutritive Sucking (NNS) to Mediate Neonates’ Pain Response from Venous Puncture (Quasi-Experiment in One Private Hospital in Surabaya) - Purnama, Ni Luh Agustini; Lestar, Ni Nyoman Wahyu; Kristalisa, Dana; Suryandari, CH.R. Yeni; Suryandari, CH.R. Yeni (International Journal of Psychosocial Rehabilitation, 2020)
Pain often occurs in neonates when venous puncture is performed during hospitalization. If pain persists for a long time, it can interfere with the process of growth and subsequent development. Nonpharmacological actions that can be undertaken to minimize pain are by giving 30% sucrose or NNS. The study aimed to identify differences in neonatal pain responses among those who received 30% sucrose and NNS. The research design used was a quasi-experimental post-test only control group design using a consecutive sampling technique; the independent variables were 30% sucrose administration and NNS while the dependent variable was neonatal pain response. The research sample was 36 respondents, namely 12 respondents who received 30% sucrose and 24 respondents who received NNS. The pain scale used was the Neonatal Infant Pain Scale (NIPS). The results showed that the average pain score in the 30% sucrose group was 1.5 and the NNS group was 3.7 with the Mann Whitney nonparametric statistical test p-value = 0.006. There are differences in neonatal pain response obtained with 30% sucrose and NNS. Pain management is very important for neonates considering the adverse effects, so to reduce pain optimally we have to undertake pain management using the 30% sucrose method or the NNS method.